Introduction from the Guest Editor: The Many Facets of Heme Oxygenase - Abraham, Nader G. (Current Neurovascular Research, 2005)
This volume of hot topics is dedicated to Attallah Kappas, M.D., former Vice President of The Rockefeller University Hospital and Professor of Pharmacology, for his contribution in developing an overall approach to understanding the significant role of the heme oxygenase system. Dr. Kappas' laboratory was the first to purify rat heme oxygenase (HO) and describe the molecular weight of this fascinating protein. HO can be considered as both a bad guy and a good guy. It can be bad protein, such as in hyperbilirubinemia or, more commonly, jaundice. Dr. Kappas' laboratory was the first to develop HO inhibitors, such as SnMP. Now, SnMP is the preferred therapy of choice for hyperbilirubinemia. In collaboration with his peers, including myself, Dr. Kappas has helped to demonstrate that HO can also be a good protein. It is an important regulator for cell cycle progression and its induction in diabetes renders the endothelium to be cytoprotective. HO has been shown to be important in attenuating the overall production of reactive oxygen species (ROS) through its ability to degrade heme and to produce carbon monoxide (CO) and bilirubin. Excess free heme catalyzes the formation of ROS, which may lead to endothelial cell (EC) dysfunction as seen in numerous pathological conditions, such as neurovascular disease, degenerative disease and hypertension as well as ischemia/reperfusion injury. The upregulation of HO-1 through the use of pharmaceutical agents such as metalloporphyrins and through site- and organ-specific targeted gene transfer has become a powerful tool for studying the role of this enzyme in the treatment of various cardiovascular diseases and diabetes. The ability to upregulate the HO-1 gene using gene transfer or pharmacological agents may offer a therapeutic strategy for treating neurovascular and cardiovascular disease in the future. This volume discusses, for the first time, the implications of HO-1 during the early stages of cardiovascular system development and suggests that HO-1 gene expression may prevent the onset of different pathological conditions. Furthermore, it provides the basis for future studies, at the basic science level, regarding the effect of HO-1-derived CO and bilirubin to bypass the induction of HO-1. We are convinced that this volume will be a useful reference for scientists and investigators who are interested in the study of the HO system.